PERANCANGAN ENTERPRISE ARCHITECTURE SISTEM INFORMASI ARSIP KPP PRATAMA SUKABUMI DENGAN PENDEKATAN ZACHMAN FRAMEWORK - Riska Fitria Rahmat; Arny Lattu; Anton Permana (Program Studi Sistem Informasi, Universitas Banten Jaya, 2026)
Sukabumi Pratama Tax Service Office (KPP) is a government agency that has a high need for efficient archive management. However, the archiving process that is still carried out conventionally causes obstacles in searching, monitoring, and managing documents. To answer these problems, an Enterprise Architecture of an archiving information system was designed using the Zachman Framework approach, which involves six perspectives consisting of Planner, Owner, Designer, Builder, Sub-Constructor, and Functioning System and six columns including What, How, Where, Who, When, and Why. This study developed a system concept and user interface design into a prototype by applying the Zachman Framework across all perspectives. The result is a design for an archiving system that aligns with the organizational structure and operational workflow of the Tax Office. Testing of the prototype was carried out using the System Usability Scale (SUS) method invoiling 7 respondents from 6 departmen, resulting in an average score of 90 which is classified as Grade A (excellent) indicating that the system can be well received by users, is well structured, and is ready to be implemented into a functional system to support the archiving process in the Sukabumi Pratama Tax Service Office (KPP) environment.